Ligand-Free, Copper-Catalyzed Ullmann-Type C–N Coupling: Regioselective Synthesis of Azole-Substituted Imidazo[1,2-a]pyridines - Kaswan, Pinku; Pericherla, Kasiviswanadharaju; Kumar, Anil (Synlett, 2013)
A simple and highly efficient protocol for the regioselective synthesis of azole-substituted imidazo[1,2-a]pyridines has been developed using a ligand-free, copper-catalyzed Ullmann-type C–N coupling of 2-(2-bromophenyl)imidazo[1,2-a]pyridines with different azoles and in situ generated 1,2,3-triazoles. The reactions proceeded smoothly to furnish azolo-imidazo[1,2-a]pyridines in good to excellent yields (65–96%).
Keywords: copper; ligand-free C–N coupling; imidazo[1,2-a]pyridines; 1,2,3-triazole; CuAAC; tandem reaction